The Return on Investment of Orthopaedic Fellowship Training: A Ten-year Update. Issue 12 (15th June 2020) - Mead, Matthew; Atkinson, Theresa; Srivastava, Ajay; Walter, Norman
Abstract : Background: Over 90% of graduating orthopaedic residents now pursue fellowship training, and only 15% of practicing orthopaedic surgeons now characterize themselves as generalists. Fellowship training has significant financial effects due to both opportunity cost of that year of training and changes in compensation throughout one's career. The purpose of this study was to estimate the financial return on investment by pursuing additional training in an orthopaedic fellowship versus general practice. Methods: Using described techniques of financial analysis, net present value (NPV), internal rate of return (IRR), and break-even point were estimated over the average working career length of an orthopaedic surgeon. Compensation data were drawn from the American Medical Group Association physician compensation surveys. Seven fellowships were studied and referenced to a career in general orthopaedic practice. Results: Fellowship training in spine surgery yields the highest return on investment with a break-even point of 5 years. Adult reconstruction has a positive NPV and IRR, but when corrected for number of hours worked per week offers no productivity advantage to general practice. Sports medicine and trauma offer neutral returns, but when corrected for work hours, NPV and IRR both become negative. Hand, pediatrics, and foot and ankle never break even following the loss of compensation realized during fellowship year. Discussion: The recent trend across all medical specialties has been for increased fellowship training and subspecialization. There are numerous reasons to pursue fellowship training, both personal and financial. This study presents an updated estimate of the financial impact of fellowship training in orthopaedics. This analysis demonstrates that selecting different fellowships can generate positive, negative, or neutral financial returns. This study has the potential to influence residents' decisions to pursue general practice versus fellowship training and identifies economic drivers, which may lead to preferential pursuit of certain subspecialties.